Fetuin B links vitamin D deficiency and pediatric obesity: Direct negative regulation by vitamin D. Issue 182 (September 2018) - Walker, Gillian E.; Follenzi, Antonia; Bruscaggin, Valentina; Manfredi, Marcello; Bellone, Simonetta; Marengo, Emilio; Maiuri, Luigi; Prodam, Flavia; Bona, Gianni
Graphical Abstract: Highlights: via proteomics, FETUB was identified/confirmed to be higher in VDD obese children. VD can directly downregulate hepatocellular FETUB synthesis in vitro . VDR silencing in vitro releases FETUB, suggesting VDR is a negative regulator. VD-supplementation to juvenile mice for 6 weeks, reduced circulating FETUB in vivo . Plasma FETUB levels likely depend on other VD-responsive tissues, with the liver. Abstract: Vitamin D (VD) deficiency (VDD) correlates to obesity, with VD a recognized mediator of metabolic diseases. From a previous proteomic study identifying adiponectin as a link between VDD and pediatric obesity, herein we analysed another protein (SSP2301) increased with VDD. A focused 2D-electrophoretic analysis identified 4 corresponding plasma proteins, with one predicted to be fetuin B (FETUB). FETUB was studied due to its emerging role in metabolic diseases and cytogenetic location (3q27.3) with adiponectin. Results were confirmed in obese children, where plasma FETUB was higher with VDD. A direct effect by 1α, 25-(OH)2D3 on hepatocellular FETUB synthesis was observed, with a time and dose dependent reduction. Further, we demonstrated the VD-receptor (VDR) is key, with FETUB "released" with VDR silencing. Finally, VD supplementation (6weeks) to juvenile mice fed a standard diet, reduced plasma FETUB. Only at 22weeks did liver FETUB correspond to plasma FETUB, highlighting the contribution of other VD-responsive tissues. Overall, FETUB is a key protein linking VDD to pediatric obesity. With an emerging role in metabolic diseases, we demonstrate that VD/VDR directly regulate FETUB.